Factors Affecting the Efficiency of Inventory Management of Janapriya Multiple Campus, Pokhara - Bhandari, Hari Bahadur (Janapriya Journal of Interdisciplinary Studies, 2018)
Each and every organization needs inventories to perform day to day activities to achieve set objectives. This study entitled 'factors affecting the efficiency of inventory management of janapriya multiple campus, pokhara' is to assess the factors that affect on inventory management of the campus. Basically, the study is based on primary data including 21 sample out of total population 28. Stratified random sampling is used to select a sample size of 21 respondents. Structured questionnaire and other official documents are used to collect data from primary sources. Samples were three groups of office staff. Group wise distribution of sample was top level, middle level and assistant level. The collected data are tabulated and presented according to the needs and objectives of the study. Descriptive statistics of mean and standard deviation were used for data analysis. Factors related with proper record keeping of inventory, financial resources, skill possessed by store staff and bureaucratic procurement procedure positively affect on the effectiveness of inventory management. Proper inventory record, stock information and competent & qualified store employees are very important for the effectiveness of inventory management. Sufficient fund, skillful store clerks, training and development for store staff, few quality suppliers and easy process of budget release are inevitable for superior inventory management. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), page: 78-87